(untitled) (Asian Journal of Ethnobiology, 2025)
Abstract. Utami AS, Torimbanu AR, Saputra AF, Aulia AA, Utomo AN, Iskandar J, Naim DMd., Setyawan AD. 2025. Diversity of natural food coloring plants in the city of Surakarta, Central Java, Indonesia. Asian J Ethnobiol 8: 92-103. The use of plant-derived food colorants is a longstanding culinary tradition in Indonesia, reflecting both ecological knowledge and cultural heritage. This study aimed to document and analyze the diversity of natural food coloring plants used in Surakarta City, Central Java, and to examine their cultural relevance, usage patterns, and conservation status. A total of 137 respondents across three urban villages—Mojosongo, Keprabon, and Baluwarti—were selected purposively and interviewed using ethnobotanical approaches including field visits and visual confirmation. Seventeen plant species from 13 families were identified as sources of eight major color types: yellow, green, red, purple, brown, white, orange, and blue. The most frequently used species included Curcuma longa, Pandanus amaryllifolius, and Clitoria ternatea, with coloring parts ranging from flowers and leaves to rhizomes and wood sap. While some plants were cultivated at home, others were purchased from traditional markets. The majority of species were classified as Least Concern, but one species (Caesalpinia sappan) was listed as Vulnerable, and several others remained unevaluated or Data Deficient. The results highlight how gender, age, and spatial context influence knowledge transmission, with older women, who play a central role, emerging as key custodians of biocultural knowledge. Although urbanization poses a threat to the sustainability of this knowledge, opportunities exist for revitalization through home gardening, school-based learning, and community-based conservation efforts. The study underscores the importance of safeguarding biocultural knowledge in rapidly modernizing urban environments as part of resilient food and cultural systems.